Analisis Penerapan Standar Akuntansi Pemerintah Berbasis Akrual Pada Peraturan Pemerintah No. 71 Tahun 2010 dalam Penyajian Laporan Keuangan Sekretariat UAPPA/B-W Kementrian Pertanian Provinsi Nusa Tenggara Barat - Asmiputri, Rofika; Jati, Ahmad Waluya (Jurnal Reviu Akuntansi dan Keuangan)
This research aims to analyze the suitability of applying the accrual-based accounting standards(Government Regulation No. 71 year 2010) with the presentation of the financial statements theaccounting Unit of the Auxiliary Budget Users/Merchandise area (UAPPA/B-W) Ministry TheAgricultural Province Of NTB. This study describes the application of Accrual Based on SAP PPNo. 71 Year 2010 using data from the results of the interviews, the balance sheet, the reportrealization of budget, income and Expenditure Information Accrual and notes to financial statements, other reports that support the theme of the research, and the information contained in thewebsite BPTP NTB. Technique of data analysis that is done is by reviewing the policies andprocedures as well as the components of the preparation of the financial statements and identifyfactors that support and hinder the implementation of SAP-based Akual. The results of thisresearch show that the presentation of the financial statements the accounting Unit of the Auxiliary Budget Users/Merchandise area (UAPPA/BW) of the Ministry of Agriculture of the province ofNusa Tenggara Barat were in accordance with the rules contained in the regulations GovernmentNo. 71 the year 2010 about Accrual-based Government accounting standards.Keyword : Acrual-based,PP No 71,UAPPA/BW